Pragmatics Presupposition Triggers inReligion Discourse (Raparin Journal of Humanities (RJH), 2025)
Pragmatics Presupposition Triggers is considered one of the dimensions of dialogic inquiry widely used in daily conversations and across all linguistic expressions, including speeches. The Friday sermon dedicated to discussing the topic of drugs, delivered by Mullah) Harbi Tetou ( on March 4, 2022, in Duhok, served as a research sample aimed at extracting types of pre-assumption generators in dialogic inquiry. The research hypothesis explored the extent to which we find pre-assumption generators in discourse? The speaker relied on conveying his message through which type of Pragmatics Presupposition Triggers, and which types of Pragmatics Presupposition Triggers are most commonly used in discourse? The results of this research indicate that this speech can be considered educational. The speaker frequently used interrogative form pre-assumption generators to engage the audience and influence them.